Letter: combination of biologics in inflammatory bowel diseases. Authors' reply. Issue 3 (13th July 2020) - Yang, Edward; Panaccione, Nicola; Whitmire, Natalie; Dulai, Parambir S.; Vande Casteele, Niels; Singh, Siddharth; Boland, Brigid S.; Collins, Angelina; Sandborn, William J.; Panaccione, Remo; Battat, Robert
Abstract : LINKED CONTENT This article is linked to Yang et al and Fumery et al papers. To view these articles, visit https://doi.org/10.1111/apt.15719 and https://doi.org/10.1111/apt.15891 .